Diseño, Programación E Implementación De Una Red De Plc Rs 485, Caso Práctico: Laboratorio De Automatización Industrial En Una Institución De Educación Superior - Iván Mesias Hidalgo Cajo; Saul Yasaca Pucuna; Byron Geovanny Hidalgo Cajo; Pedro Rolando Salazar Andrade; Diego Patricio Hidalgo Cajo (European Scientific Journal, ESJ, 2018)
The objective of the research is to develop a network system based on PLC RS-485T, to monitor a mechatronic equipment called Assembly of Parts, in the Industrial Automation Laboratory of the School of Systems Engineering of the Polytechnic School of Chimborazo. The research was developed based on the scientific method, and two Twido 20DTK PLCs were used, one PLC as Master and another PLC as Slave. The software for the monitoring of the network was carried out in the software called Labview version 7.1 and the TwidoSoft version 3.5 for the PLC coding. The communication between the different Twido 20DTK PLCs was obtained under the Labview 7.1 monitoring graphical interface; applying the data transfer in the RS-485T PLC network, improving the data transmission speed and avoiding that they are lost during the transmission, obtaining 70% the Ethernet network and 95% the industrial network, checking the reliability 75% in the Ethernet network and 100% in the industrial network, the speed in 75% in the Ethernet network and 100% in the industrial network and prevents the loss of information by 50% in the Ethernet network and the 100% in the industrial network; demonstrating the values obtained in an RS-485 Ethernet network. The developed system is applied sequentially, each time the sensor detects movement of an object (piece of the pallet) during the assembly, which was reflected in the user interface, changing color. In addition to the use of Modbus technology, the integration and communication of the PLC's was achieved, thus improving learning by observing in the computer the process of assembling parts.